The new pandemic for SARS-CoV-2: epidemiology and the response of the peruvian health system - Gonzales Menis, Gabriela Alejandra (2021)
The World Health Organization declared the new disease (COVID-19) a pandemic on March 12, and as of January 13, 2021, there were more than 86 million confirmed cases of COVID-19 have been recorded worldwide. In the world, at the Latin American level, Peru ranks fifth with 1,082,907 confirmed cases, presenting a fatality rate of 3.63%. In the same way, the Peruvian State, in response to this COVID-19 disease, issued a regulation through the Ministry of Health (MINSA) in order to counteract the contagion and number of deaths. Although Peru was one of the first countries in the region to implement restrictive measures in the first months, it was one of the most affected; together with the guidelines implemented by MINSA institutions, they did not reflect the expected results, observing the availability of 141 beds of Intensive Care Unit (ICU) nationwide as of January 21, 2021 and Peru in fifth place in the number of infections in Latin America with 1,082,907 confirmed cases and 39,274 deaths with a fatality rate of 3.63%.